The Well-Being of Carers of Older Aboriginal People Living in the Kimberley Region of Remote Western Australia: Empowerment, Depression, and Carer Burden. (July 2021) - LoGiudice, Dina; Josif, Cathryn M.; Malay, Roslyn; Hyde, Zoë; Haswell, Melissa; Lindeman, Melissa A.; Etherton-Beer, Christopher; Atkinson, David; Bessarab, Dawn; Flicker, Leon; Smith, Kate
Objective: To describe demographic features and well-being of carers of Aboriginal Australians aged ≥45 years in remote Western Australia.Method: Carer burden, empowerment, and depression were assessed in 124 Aboriginal carers in four remote Aboriginal communities.Results: Carers were aged 38.8 ± 15.0 years, 73.4% were female, and 75.8% were children or grandchildren of the person cared for. The mean Zarit-6 score was 3.7 ± 3.6. Attending high school (odds ratio [OR] = 0.3; 95% confidence interval [CI] = [0.1, 0.7]) and feeling empowered (OR = 0.2; 95% CI = [0.1, 0.8]) were inversely associated with carer burden; female carers were less likely to feel empowered (OR = 0.4; 95% CI = [0.2, 0.9]); and empowerment was inversely associated with depression (OR = 0.3; 95% CI = [0.1, 0.7]).Discussion: Aboriginal carers in remote communities are relatively young and most are children or grandchildren. Carer burden was lower than anticipated. However, existing tools may not adequately measure Aboriginal perspectives. Education and empowerment are key factors which support programs must consider.